2006
DOI: 10.2140/agt.2006.6.351
|View full text |Cite
|
Sign up to set email alerts
|

Non-isotopic Heegaard splittings of Seifert fibered spaces

Abstract: We find a geometric invariant of isotopy classes of strongly irreducible Heegaard splittings of toroidal 3-manifolds. Combining this invariant with a theorem of R Weidmann, proved here in the appendix, we show that a closed, totally orientable Seifert fibered space M has infinitely many isotopy classes of Heegaard splittings of the same genus if and only if M has an irreducible, horizontal Heegaard splitting, has a base orbifold of positive genus, and is not a circle bundle. This characterizes precisely which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…For toroidal manifolds, Morimoto and Sakuma [26] have found a number of tunnel number one knot complements and Bachman and Derby-Talbot [3] have found Seifert fibered spaces with an infinite number of homeomorphic, non-isotopic Heegaard splittings. For all these Heegaard splittings, the image of i has infinite index.…”
Section: The Mapping Class Groupmentioning
confidence: 99%
“…For toroidal manifolds, Morimoto and Sakuma [26] have found a number of tunnel number one knot complements and Bachman and Derby-Talbot [3] have found Seifert fibered spaces with an infinite number of homeomorphic, non-isotopic Heegaard splittings. For all these Heegaard splittings, the image of i has infinite index.…”
Section: The Mapping Class Groupmentioning
confidence: 99%
“…To complete the proof, isotope F so as to remove any loops that are trivial in both F and S. Bachman and Derby-Talbot [2006] pointed out that after these trivial loops are removed, S \ F is a pair of compressing disks for F whose boundaries, when made transverse, intersect at four points. These compressing disks are on opposite sides of F and are contained in the regular neighborhood R. Any compressing disk for F \ R is disjoint from each of the disks in S \ F. Because ( , H 1 , H 2 ) is strongly irreducible and F is isotopic to , the surface \ R must be incompressible in M \ R.…”
Section: Toroidal Summandsmentioning
confidence: 99%
“…Bachman and Derby-Talbot [2006] showed that any Seifert fibered space that admits a strongly irreducible horizontal splitting admits infinitely many isotopy classes of horizontal splittings. We improve their analysis to show the following:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Section 5 we survey known work that gives quite satisfactory restrictions to phenomena (1) and (2). We also give an extended example: Dehn filling on a torus knot exterior, for which we have almost complete knowledge.…”
Section: Introductionmentioning
confidence: 99%